TEACHER TALK IN CLASSROOM INTERACTION IN TEACHING SPEAKING FOR THE FIRST GRADE STUDENTS AT SMA NEGERI 20 MEDAN - Nur Aini Villy; Siti Aisah Ginting; Syamsul Bahri (Universitas Negeri Medan, 2024)
This study aims at analyzing features of teacher talk in teaching speaking. The subject of this study were English Teacher and 40 students at first grade of SMA Negeri 20 Medan. The data were collected through the following: observation, and audio recording. In this research, the FLINT is used to identify the categories of teacher talk occur during the learning process. Moreover, this study is conducted in the form of descriptive qualitative research where the researcher as the non-participant observer on the classroom. From the data that has been taken, it is obtained that the categories of teacher talk used by the teacher in teaching speaking in the first grader of SMA Negeri 20 Medan are deals with feeling, praises or encourages, jokes, uses ideas of students, repeats students response verbatim, ask questions, gives information, corrects without rejection, give direction, criticizes student behavior, and Criticize student response. The finding of the study showed that there are eleven features of teacher talk occur in English classroom interaction and the dominant feature of teacher talk was ask questions (40.2%). The feature of teacher talk which is dominantly used by the teacher help students more active in the class because the teacher gave the oppurtunity to the learners to deliver their ideas, and try their ability in speaking skill.